Challenges, Coping Strategies, and Social Support among Breast Cancer Patients in Ghana. (25th February 2020) - Boatemaa Benson, Ruth; Cobbold, Bernice; Opoku Boamah, Ellen; Akuoko, Cynthia Pomaa; Boateng, Daniel
Abstract : Background . Despite the high incidence and mortality rate of breast cancer (BC) in Ghana, little attention has been given to the issue of how adult women cope with having BC. The aim of this study was to explore the challenges, coping strategies, and support systems among women diagnosed with BC in Ghana. Methods . A descriptive cross-sectional study was conducted from February to August 2017 at the Komfo Anokye Teaching Hospital (KATH), Ghana. A systematic random sampling technique was used to select 202 women with a confirmed diagnosis of BC. Coping strategies of women with BC were assessed using the Brief-COPE. The associations between sociodemographic characteristics, social network/support, and coping strategies were assessed using linear regression models. Results . The most and least adopted active coping strategies were religious coping and humors, respectively. Self-distraction and substance use were the most and least adopted avoidant coping strategies, respectively. Spouses and children offered the most support to women with BC; having support from 5 or more sources was associated with higher mean active coping (beta [ β ] 1.14; 95% CI 0.66 to 1.62) and avoidant coping ( β 1.46; 95% CI 0.98 to 1.94), as compared with having <2 sources of social support. Conclusion . This study demonstrates that women diagnosed with BC in Ghana adopt varied coping strategies to deal with these challenges. The forms of coping strategies adopted by women diagnosed with BC are influenced by the extent of social support received. Psychosocial counseling and support should be an integral part of BC management. Exploring and including social networks could play an important role in the management of BC in Ghana.